Strategies to improve the solubility and stability of stilbene antioxidants: a comparative study between cyclodextrins and bile acids - Silva, Filomena (2014)
Aiming at the development of an active food packaging, the goal of this study was to increase stilbenes (resveratrol (RV), pterostilbene (PT) and pinosylvin (PS)) aqueous solubility and stability using hydropropyl-cyclodextrins (HP-CDs) and bile salts. To evaluate stilbene concentration, an HPLC-DAD method was validated. Stilbene solubility was improved by the formation of inclusion complexes and micellar systems with higher solubility values obtained for the inclusion complexes with cyclodextrins. Inclusion complexes revealed a 1:1 stoichiometry for RV and PT and a 1:2 for PS. Solid state characterisation was carried out using X-ray diffraction, Fourier transform infrared spectroscopy and differential scanning calorimetry. 1H NMR studies were also performed to characterise the prepared complexes. Photostability studies revealed that CDs were able to increase stilbene photostability at 4 °C. This work showed that stable stilbene solutions can be achieved using hydroxypropyl-CDs, contributing for their incorporation in several materials for the food and pharmaceutical industries.